Tax Breaks for Swing States? Political Bargaining, Targeted Policies, and Firm Outcomes - Raina, Sahil; Xu, Sheng-Jun (The Review of Corporate Finance Studies, 2026)
Abstract We examine how firms are affected by the political bargaining power of their headquarters’ region. Exploiting variation in the strategic importance of swing states stemming from shifting partisan balance in the U.S. Senate, we find that corporate valuations and investments positively respond to increases in regional political influence. We verify the valuation findings using an event study based on the 2021 Georgia runoff election that unexpectedly produced a 50-50 balance in the Senate. We investigate potential policy mechanisms and find that tax incentives constitute the most likely channel through which firms benefit from the political bargaining power of their headquarters’ region.